Fast and low-noise tunnelling current measurements for single-molecule detection in an electrolyte solution using insulator-protected nanoelectrodes. Issue 12 (24th January 2017) - Morikawa, Takanori; Yokota, Kazumichi; Tsutsui, Makusu; Taniguchi, Masateru
Abstract : Low-noise and fast tunnelling current measurements were performed using insulator-coated nanoelectrodes for single-nucleotide detection. Abstract : Reliable ways of DNA sequencing by tunnelling current require low-noise and high-speed measurements of tunnelling current in aqueous environments. Here we report a use of insulator-protected nanoprobes for achieving 7.6 pA rms noise at 50 kHz sampling rates in an electrolyte solution. We utilized dielectric-covered mechanically-controllable break junctions to create a pair of nano-exposed insulator/Au coaxial electrodes closely separated by 1 nm. We observed insulator layer thickness dependent noise levels, which was attributed to decreased capacitance through replacing capacitive electric double layers by the low- k dielectrics. We also demonstrated the detection of sharpened features in tunnelling current signatures that reflect dynamic motions of single-nucleotides in the electrode gaps by virtue of suppressed smearing effects in the low-capacitance nanoelectrode system.